The Effect of Stable Manure and Seedling Number on Growth and Yield of Black Rice (Oryza sativa L. Indica) - Okti Herliana; Ida Widiyawati; Sapto Nugroho Hadi (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Black rice is one of fungtional food sources. The obstacle of its cultivation is availability of qualified seeds and organic fertilizers input. This research aimed to determine the effect of stable manure on growth and yield of black rice, to observe the effect of seddling number per planting hole and to obtain the best combination of stable manure and seedling number on the growth and yield of black rice. The research was conduct in rice field on Karanglewas Kidul village, Karanglewas district, Banyumas, Central Java during April until September 2016. This research used a split plot design, with 3 repetition. The main plot was three type of stable manure (chiken, goat and cow), while the subplot was seddling number (1, 2 and 3). Data was analyzed using ANOVA and DMRT at p 0.05 level. The results showed that chicken manure gave the highest productivity rice of 5.15 tons ha-1. The 1 seedling each hole gave the highest result on panicle length and grain number per panicle. The better combination treatment was chicken manure and three seedling per planting hole wich gave the highest grain yield of 5.38 tons ha-1.